Does concentration drive the scatter in the stellar-to-halo mass relation of galaxy clusters?. Issue 4 (17th June 2021) - Zu, Ying; Shan, Huanyuan; Zhang, Jun; Singh, Sukhdeep; Shao, Zhiwei; Chen, Xiaokai; Yao, Ji; Golden-Marx, Jesse B; Cui, Weiguang; Jullo, Eric; Kneib, Jean-Paul; Zhang, Pengjie; et al.
ABSTRACT: Concentration is one of the key dark matter halo properties that could drive the scatter in the stellar-to-halo mass relation of massive clusters. We derive robust photometric stellar masses for a sample of brightest central galaxies (BCGs) in SDSS redmapper clusters at 0.17 < z < 0.3, and split the clusters into two equal-halo mass subsamples by their BCG stellar mass $M_*^{BCG}$ . The weak lensing profiles ΔΣ of the two cluster subsamples exhibit different slopes on scales below $1\, h^{-1}\, Mpc$ . To interpret such discrepancy, we perform a comprehensive Bayesian modelling of the two ΔΣ profiles by including different levels of miscentring effects between the two subsamples as informed by X-ray observations. We find that the two subsamples have the same average halo mass of $1.74× 10^{14}\, h^{-1}\, M_{\odot }$, but the concentration of the low-$M_*^{BCG}$ clusters is $5.87_{-0.60}^{+0.77}$, ∼1.5σ smaller than that of their high-$M_*^{BCG}$ counterparts ($6.95_{-0.66}^{+0.78}$ ). Furthermore, both cluster weak lensing and cluster-galaxy cross-correlations indicate that the large-scale bias of the low-$M_*^{BCG}$, low-concentration clusters are ${\sim}10{{\ \rm per\ cent}}$ higher than that of the high-$M_*^{BCG}$, high-concentration systems, hence possible evidence of the cluster assembly bias effect. Our results reveal a remarkable physical connection between the stellar mass within $20{-}30\, h^{-1}\, {kpc}$, the dark matter mass within ${\sim}200\, h^{-1}\, {kpc}$, and the cosmic overdensity on scales above $10\, h^{-1}\, Mpc$, enabling a key observational test of theories of co-evolution between massive clusters and their central galaxies.